2002
DOI: 10.1021/np010545m
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpenoids fromTithonia diversifoliawith Potential Cancer Chemopreventive Activity

Abstract: Activity-guided fractionation of an ethyl acetate extract of the aerial parts of Tithonia diversifolia, using an antiproliferation bioassay performed with human colon cancer (Col2) cells, led to the isolation of three new sesquiterpenoids, 2alpha-hydroxytirotundin (1), tithofolinolide (2), and 3alpha-acetoxydiversifolol (3), along with eight known sesquiterpene lactones, 3beta-acetoxy-8beta-isobutyryloxyreynosin (4), tagitinin C (5), 1beta,2alpha-epoxytagitinin C (6), 4alpha,10alpha-dihydroxy-3-oxo-8beta-isobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 18 publications
4
76
0
7
Order By: Relevance
“…Sesquiterpene lactones are phytochemicals derived from Chinese medicinal herbs, and have been demonstrated previously to have anti-neoplastic and anti-inflammatory activities (8). Costunolide is a well-known sesquiterpene lactone and a number of previous studies have shown that it has a broad spectrum of cytotoxicity against human cancer cell lines of different origins (6,18,(20)(21)(22)26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sesquiterpene lactones are phytochemicals derived from Chinese medicinal herbs, and have been demonstrated previously to have anti-neoplastic and anti-inflammatory activities (8). Costunolide is a well-known sesquiterpene lactone and a number of previous studies have shown that it has a broad spectrum of cytotoxicity against human cancer cell lines of different origins (6,18,(20)(21)(22)26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Sesquiterpene lactones are predominantly isolated from members of the Compositae and Magnoliaceae plant families, and have attracted widespread attention due to their anti-tumor and anti-inflammatory activity, (8,9). Costunolide, a sesquiterpene lactone, which is isolated from Chinese herb Saussurea lappa, is a popular herbal remedy, with anti-ulcer (10), anti-inflammatory (11), anti-fungal (12) and anti-viral properties (13).…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical profile of TDLM revealed high levels of flavonoids and phytin [25]. Moreover, sesquiterpene lactones in TDLM were reported to be free radical scavengers [26]. It is therefore conceivable that these components may have competed with haemoglobin (Hb) in red blood cell (RBC) for oxygen, resulting in hypoxea which stimulated synthesis and RBC production.…”
Section: 52mentioning
confidence: 99%
“…Borges et al (2006) described the presence of derivatives anthraquinones produced by Phoma sorghina, and endophytic fungus associated to a medicinal plant Tithonia diversifolia (Asteracea). This plant extracts are used for the treatment of malaria, diarrhea, fever, hepatitis and wounds (Gu et al, 2002, Cos et al, 2002. There are also attributed anti-inflammatory, amebic, antispasmodic, antifungal, antibacterial and antiviral activities (Goffin et al, 2002, Cos et al, 2002.…”
Section: Biological Activity From Medicinal Plants Endophytesmentioning
confidence: 99%